L Training on Creating Educational Anti-Corruption Flyers Using the Canva App for Students at Pattimura University Laboratory Junior High School - Louisa M Metekohy; Agustinus Nindatu; Jumiati Tuharea; Jurgen R Litualy (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
Today’s education requires students to possess knowledge and be able to use technology in their learning, such as the Canva app, which they can then use to create anti-corruption flyers. This activity equips students with basic graphic design skills through Canva to creatively promote anti-corruption values within the school environment. This community service activity employs participatory training methods and Project-Based Learning. Students at the Pattimura University Laboratory Junior High School were educated on the values of integrity, followed by hands-on practice designing anti-corruption flyers using the Template feature. The results of the activity demonstrate that students can use the application effectively, as evidenced by their creativity in selecting and finalizing designs, as well as their ability to craft anti-corruption narratives, resulting in flyers suitable for display on school bulletin boards and social media.